What Is the Clinical Impact of Stress CMR After the ISCHEMIA Trial? - Pezel, Théo; Silva, Luis Miguel; Bau, Adriana Aparecia; Teixiera, Adherbal; Jerosch-Herold, Michael; Coelho-Filho, Otávio R. (Frontiers in Cardiovascular Medicine, 2021)
After progressively receding for decades, cardiovascular mortality due to coronary artery disease has recently increased, and the associated healthcare costs are projected to double by 2030. While the 2019 European Society of Cardiology guidelines for chronic coronary syndromes recommend non-invasive cardiac imaging for patients with suspected coronary artery disease, the impact of non-invasive imaging strategies to guide initial coronary revascularization and improve long-term outcomes is still under debate. Recently, the ISCHEMIA trial has highlighted the fundamental role of optimized medical therapy and the lack of overall benefit of early invasive strategies at a median follow-up of 3.2 years. However, sub-group analyses excluding procedural infarctions with longer follow-ups of up to 5 years have suggested that patients undergoing revascularization had better outcomes than those receiving medical therapy alone. A recent sub-study of ISCHEMIA in patients with heart failure or reduced left ventricular ejection fraction (LVEF <45%) indicated that revascularization improved clinical outcomes compared to medical therapy alone. Furthermore, other large observational studies have suggested a favorable prognostic impact of coronary revascularization in patients with severe inducible ischemia assessed by stress cardiovascular magnetic resonance (CMR). Indeed, some data suggest that stress CMR-guided revascularization assessing the extent of the ischemia could be useful in identifying patients who would most benefit from invasive procedures such as myocardial revascularization. Interestingly, the MR-INFORM trial has recently shown that a first-line stress CMR-based non-invasive assessment was non-inferior in terms of outcomes, with a lower incidence of coronary revascularization compared to an initial invasive approach guided by fractional flow reserve in patients with stable angina. In the present review, we will discuss the current state-of-the-art data on the prognostic value of stress CMR assessment of myocardial ischemia in light of the ISCHEMIA trial results, highlighting meaningful sub-analyses, and still unanswered opportunities of this pivotal study. We will also review the available evidence for the potential clinical application of quantifying the extent of ischemia to stratify cardiovascular risk and to best guide invasive and non-invasive treatment strategies.